2023
DOI: 10.1021/acs.orglett.3c00571
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Cyanomethyl Indane Derivatives via Pd-Catalyzed Alkene Difunctionalization Reactions of Alkyl Nitriles

Abstract: The synthesis of indanes bearing substituted cyanomethyl groups at C2 is achieved through Pd-catalyzed coupling reactions between 2-allylphenyl triflate derivatives and alkyl nitriles. Related partially saturated analogues were generated from analogous transformations of alkenyl triflates. The use of a preformed BrettPhosPd(allyl)(Cl) complex as a precatalyst was essential for the success of these reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Following the seminal contributions from the Stahl group and our group, several famous research teams have substantially contributed to this developing field through innovative approaches and deep mechanistic insights . Although nonstereoselective Wacker-type functionalizations with C–H nucleophiles have been successfully implemented, research on their asymmetric versions remains limited (Scheme B) . In 2016, the Engle group reported a creative regioselective Wacker-type hydrocarbofunctionalization of internal alkenes with diverse C–H nucleophiles using a removable directing group strategy .…”
Section: Introductionmentioning
confidence: 99%
“…Following the seminal contributions from the Stahl group and our group, several famous research teams have substantially contributed to this developing field through innovative approaches and deep mechanistic insights . Although nonstereoselective Wacker-type functionalizations with C–H nucleophiles have been successfully implemented, research on their asymmetric versions remains limited (Scheme B) . In 2016, the Engle group reported a creative regioselective Wacker-type hydrocarbofunctionalization of internal alkenes with diverse C–H nucleophiles using a removable directing group strategy .…”
Section: Introductionmentioning
confidence: 99%
“…Biindenes that lack carbonyl functionality on the indene ring are relatively rare and have most commonly been prepared via carbocation intermediates or from reductive deoxygenation of the corresponding indanones . However, although relatively few biindene derivatives are known, some of these derivatives have interesting and potentially useful biological activities, including smooth muscle relaxing activity, mast cell stabilizing activity, or anti-inflammatory activity .…”
mentioning
confidence: 99%
“…We recently described a new Pd-catalyzed cross-coupling (alkene difunctionalization) reaction between nitrile nucleophiles and 2-allylphenyl triflate derivatives or related alkenyl triflates. During the course of these studies, we found that transformations of relatively bulky α-branched nitriles were generally effective (Scheme , eq 1). However, yields decreased as the size of the alkyl chain decreased, with competing direct α-arylation of the nitrile becoming increasingly problematic.…”
mentioning
confidence: 99%